If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5b + 2a + 4 = 0 Reorder the terms: 4 + 2a + 5b = 0 Solving 4 + 2a + 5b = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + 2a + -4 + 5b = 0 + -4 Reorder the terms: 4 + -4 + 2a + 5b = 0 + -4 Combine like terms: 4 + -4 = 0 0 + 2a + 5b = 0 + -4 2a + 5b = 0 + -4 Combine like terms: 0 + -4 = -4 2a + 5b = -4 Add '-5b' to each side of the equation. 2a + 5b + -5b = -4 + -5b Combine like terms: 5b + -5b = 0 2a + 0 = -4 + -5b 2a = -4 + -5b Divide each side by '2'. a = -2 + -2.5b Simplifying a = -2 + -2.5b
| -2k+28=21k+49 | | n=70 | | -9x-6=x-30 | | y=x+y/2 | | 7x+7=18x-4 | | 0=(.2-x)*(.0002-3x)*(.0002-3x)*(.0002-3x) | | x=3+0.25y | | x=3+0.25y | | 3(15)+5=5(15)-25 | | -1/3=5 | | e/6=12/4 | | 12/4=d/8 | | (z+8)(z-11)= | | -9(x-9)=(x+63) | | t=14 | | -3(1)=3 | | 10y+20x=130 | | 9x^2-18xy+8y=0 | | x+3/5=2 | | c+3/5=2 | | 18+a=16 | | 2*3x+11=6x+4 | | 9-v^2=0 | | 5/4.5=-7.18 | | y/9+7=4(y-7) | | y^2-6x-11=0 | | u^2-1u-2=0 | | (4-u^2)=0 | | 1=-3x+3 | | 6x^2-19x-3=0 | | -(9-m)=-(6m+9) | | 4x+y=112 |